Long-term impacts of nitrogen deposition on coastal plant communities. (May 2016) - Pakeman, Robin J.; Alexander, Jim; Brooker, Rob; Cummins, Roger; Fielding, Debbie; Gore, Sarah; Hewison, Richard; Mitchell, Ruth; Moore, Emily; Orford, Katy; Pemberton, Clare; Trinder, Clare; et al.
Abstract: Nitrogen deposition has been shown to have significant impacts on a range of vegetation types resulting in eutrophication and species compositional change. Data from a re-survey of 89 coastal sites in Scotland, UK, c. 34 years after the initial survey were examined to assess the degree of change in species composition that could be accounted for by nitrogen deposition. There was an overall increase in the Ellenberg Indicator Value for nitrogen (EIV-N) of 0.15 between the surveys, with a clear shift to species characteristic of more eutrophic situations. This was most evident for Acid grassland, Fixed dune, Heath, Slack and Tall grass mire communities and despite falls in EIV-N for Improved grass, Strand and Wet grassland. The increase in EIV-N was highly correlated to the cumulative deposition between the surveys, and for sites in south-east Scotland, eutrophication impacts appear severe. Unlike other studies, there appears to have been no decline in species richness associated with nitrogen deposition, though losses of species were observed on sites with the very highest levels of SOx deposition. It appears that dune vegetation (specifically Fixed dune) shows evidence of eutrophication above 4.1 kg N ha −1 yr −1, or 5.92 kg N ha −1 yr −1 if the lower 95% confidence interval is used. Coastal vegetation appears highly sensitive to nitrogen deposition, and it is suggested that major changes could have occurred prior to the first survey in 1976. Highlights: A re-survey of Scottish coastal habitats was analysed for pollution impacts. Eutrophication impacts in south-east Scotland are severe. Species loss appears more associated with sulphur deposition. Sand dune vegetation appears highly sensitive to nitrogen deposition. Functional changes in the vegetation were apparent above 4.1 kg N ha −1 yr −1 . Abstract : Coastal habitats are very sensitive to nitrogen deposition and functional changes in vegetation have been significant in more heavily polluted areas.